A Bibliometric Analysis of Mathematical Literacy Research in Indonesia Based on PISA Studies (2020–2025) - Ratu Defina Yuniar; Rohati Rohati; Marlina Marlina (MASI Mandiri Edukasi, 2025)
This study investigates the development of mathematical literacy research in Indonesia within the PISA context from 2020 to 2025. The analysis was conducted using a literature review combined with bibliometric techniques, drawing data from Publish or Perish (Google Scholar) and visualizing patterns using VOSviewer. From an initial collection of 200 publications, 25 studies were identified as relevant to the PISA framework. The bibliometric results include network visualization, which shows the clustering of key themes; overlay visualization, illustrating shifts in research focus over time; and density visualization, highlighting frequently explored topics. The findings reveal that studies on mathematical literacy in Indonesia remain primarily focused on educational themes, although an emerging interest in interdisciplinary and digital-related perspectives is evident. These results also highlight several ongoing issues, including the limited integration of PISA competencies, uneven distribution of research, and the need for stronger digital and cross-disciplinary approaches. Consequently, this study emphasizes the importance of advancing mathematical literacy research in Indonesia to address contemporary educational challenges and support the enhancement of students’ competencies.